A preliminary comparative study of rhythm systems employed within the first-year college aural skills class - Janssen, Brett Allen (Kansas State University, 2017)
The purpose of this study was to discover whether differences exist in rhythm pattern achievement of the three rhythm systems Takadimi, 1 e & a, and 1 ta te ta in introductory level aural skills classrooms. Participants (N = 27) were first-level aural skills students in three Midwest colleges. Data were collected by implementing a demographics questionnaire to obtain a descriptive profile of the participants, Gordon’s (1989) Advanced Measures of Music Audiation (AMMA) test to obtain the music aptitude level of the participants, and a researcher-designed pretest and posttest. A significant difference was unable to be determined of rhythm pattern achievement between the three systems. However, results revealed improvement of rhythm reading between the pretest and posttest for all rhythm systems. A significant difference was unable to be determined in achievement between students with low and high aptitude following instruction in a particular rhythm system. The improvements in rhythm reading suggest that progress and achievement can be independent of using any of the three rhythm systems, but further investigation with a larger sample is recommended.
Keywords: Music education; Aural skills; Rhythm systems; Music theory; Rhythm solfege